KONSEP KOSMOLOGIS GENDER, LEGALITAS DAN REALITASNYA DALAMSISTEM PRANATA SOSIAL - Zuhairansyah Arifin; Elva Zahuri (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
Gender is different betweenman andwoman based to social construction. The different of behaviorman and woman for the greater part created with agriculture social process, and little with biologic process. So, gender always to change time by time, place to place, and from one class to the other class, meanwhile the gender always permanent.The fact, in social living, appraiser for woman begin to opinion about truth in religion. The first, dogmatic opinion to place women as complementary. Second, dogmatic opinion that natural ability (potention), moral, and woman ethic very shorter. Third, materialistic opinion, patrilineal social ideology before Islam to look at lower about participation of woman in production process and public relation.